Imunidade soberana e impactos ambientais decorrentes de operações militares navais: o controle de tráfego militar na Amazônia Azul para uma defesa ambiental proativa - Silva, Susi Castro (2019)
Before regarded as a maxim on the sea, the principle of freedom of navigation is now in competition with the rights and duties conferred by the Convention on the Law of the Sea (UNCLOS) to coastal and archipelagic states. Various regulations and spatial plannings have been established on maritime spaces defined by UNCLOS. At the same time, a singularly naval arms race has been taking place since the beginning of the 21st century, and its impacts on the marine environment have been denounced by the scientific community, emerging the discussion about the need to set limits to the proliferation of armaments in the marine environment. This problem was not directly faced by UNCLOS, which, on the contrary, established sovereign immunity to warships, and other government vessels in and non-commercial servide, related to its rules on the protection and preservation of the marine environment. Given this situation, we sought to identify a balance through the adoption of proactive environmental defense measures by coastal states in their EEZs. Given the economic, environmental and geostrategic importance for Brazil of its EEZ, named ―Blue Amazon‖ by the Brazilian Navy's, it was analyzed in this thesis whether the establishment by Brazil of a maritime traffic control, for monitoring purposes of foreign naval military activities, carried out through the Blue Amazon, would be in line with the Law of the Sea. For this, we analyzed: the paradoxical relationship between sovereign immunity from the international protection of the marine environment, and the need to seek ways to overcome such a paradox; the possibility of international liability of states for damage resulting from environmental impacts caused by naval military operations; and the demand for environmental safety in the Blue Amazon. The qualitative approach and the mutually complementary deductive and inductive methods were applied, as well as the transdisciplinary dialectical reasoning, since the object of the present eminently legal research is also related to Political Science, International Relations, and the defense. In the end, the general hypothesis that the establishment of naval traffic control in relation to foreign state vessels, especially those commissioned for military operations, would be within the scope of the right of jurisdiction granted is confirmed. coastal state by UNCLOS for environmental protection purposes in the EEZ.